Unraveling the effect of redox potential on dark fermentative hydrogen production - Sim, Xue Yan; Tan, Jian Ping; He, Ning; Yeap, Swee Keong; Hui, Yew Woh; Luthfi, Abdullah Amru Indera; Abdul Manaf, Shareena Fairuz; Bukhari, Nurul Adela; Jamali, Nur Syakina (Elsevier Ltd, 2023)
Biological hydrogen production by dark fermentation is an environmentally benign alternative to the conventional fossil-based hydrogen production process. However, low biological hydrogen yields remain a major constraint to commercial production. Unraveling the metabolic pathway for hydrogen production will unlock the potential to enhance biohydrogen yield. In this regard, the key fundamentals of various important dark fermentative hydrogen-producing metabolic pathways are scrutinized in this review, including those in strict and facultative anaerobic bacteria such as Clostridia, Enterobacter, Thermotoga, and Thermoanaerobacterium. Since the hydrogen metabolic pathway is governed by a series of redox reactions during fermentation, manipulation of the redox potential not only indicates the extent of an anaerobic condition, but also affects the growth of anaerobic bacteria. This article reviews the types of hydrogen-producing bacteria and their fundamental metabolic pathways, the effect of redox potential on metabolic fluxes towards growth and hydrogen production and discusses various important redox potential control strategies. In pure culture, strict anaerobes are more suitable to grow in a more reducing environment (lower redox potential), while facultative anaerobes thrive in the presence of oxygen where the redox potential is relatively higher. Redox potential control could minimize the carbon flow towards the propionate-producing pathway by avoiding the redox potential value of around ˆ’ 280 mV. Avoiding the propionate- and lactate-producing pathways results in a higher chance of producing hydrogen via the pyruvate decarboxylation process. Overall, the review provides an all-rounded investigation on the manipulation and impact of redox potential to achieve better hydrogen production for sustainable energy resources.